Theoretical simulation and experimental verification of dynamic caustic manipulation using a deformable mirror for laser material processing. (May 2022) - Smarra, Marco; Gurevich, Evgeny L.; Ostendorf, Andreas
Highlights: Deformable mirrors can handle high average laser powers and pulse energies. Deformable mirror optical system setup for beam shaping in material processing. Diffraction free influences on the beam shape using a deformable mirror. Defocus and astigmatism control using deformable mirror for material processing. Variable beam shaping using a deformable mirror for drilling thin metal foils. Abstract: The influence of a deformable mirror on spatial light modulation in ultrafast lasers processing is demonstrated. The deformable mirror was integrated into an optical setup which contains an additional lens for generating a nearly linear focus shift in the focal plane behind the f-theta lens. The deformation of the mirror surface can be described by the Zernike terms Defocus, Astigmatism, and a combination of both, resulting in a cylindric lens behavior. The influence of the mirror surface deformation in this optical setup on the intensity distribution in the focal plane was simulated. From the simulation results, the caustic in the focal plane was calculated. The simulation results were compared to experiments using a picosecond laser with a maximum pulse energy of about 60 µJ. We demonstrate that the initial astigmatism of the raw beam can be reduced using the deformable mirror. A linear focus shift ( R 2 = 98.7 % ) and the generation of elliptical/ line intensity distributions are shown. Line intensity distribution was used to demonstrate slit drilling application in thin metal foils.